Methyl 4-amino-3-methylbenzoate - Li, Xiang (International Union of Crystallography, 2008)
In the molecule of the title compound, C(9)H(11)NO(2), the methyl C and amino N atoms bonded to the benzene ring lie in the ring plane. Intramolecular C—H⋯O hydrogen bonding results in the formation of a five-membered planar ring, which is oriented at a dihedral angle of 2.73 (3)° with respect to the benzene ring, so they are nearly coplanar. In the crystal structure, intermolecular N—H⋯O hydrogen bonds link the molecules into chains elongated along the c axis and stacked along the b axis.